Computer game approach for children with autism spectrum disorder: their engagement and social communication skills / Sara Reisi Dehkordi - Dehkordi, Sara Reisi (2015)
Autism Spectrum Disorder is characterized in three different areas by difficulties in social interaction, communication and repetitive behavior. Children with Autism Spectrum Disorder faced with difficulty in the communication skills area, which impacts their social world. Findings suggest that technology and computer devices are helpful educational aids for students with Autism. This research ongoing agenda is to find ways to design and develop an educational game on iOS platform and to test and evaluate of the effectiveness of this game. The research reported here involved 14 children with ASD, these students had problem in social communication areas and they showed improvement in social communication skills and user engagement after ten testing sessions in duration of two weeks. This research's aim was to investigate each individual child's problem regarding communication by means of design and develop an application for this purpose. By combining suitable components to engage the player and traditional psychological methods as a therapy purpose, use of proposed game encourages players to learn new things while they are working with technology. The results of this research demonstrate that the game that have been designed and developed based on the limitation of participants can promote communication skills in student and engage them in working with technology. The findings from this study reveal practices surrounding the use of computer game approach in therapy sessions and highlight important considerations for design, develop and evaluation of games which has been developed for children with Autism.